Respuesta :

cg2929
If x+y=4 then Y=4-x so 4x +3(4-x)=13 is 4x + 12 - 3x = 13 then add your x's together and you get 1x then subtract 12 from each side and you are left with 1x=1 so x=1 then plug 1 in for x in the original formula and you get 4(1) +3y =13 you then subtract 4 from each side and get 3y = 9 divide each side by 3 and you get y=3
For substitution, you need to solve one equation in terms of the other. The easiest one would be the second one. So subtract over the x giving: y=4-x. From here you SUBSTITUTE it into the other one. 4x+3(4-x)=13 Distribute: 4x+12-3x=13 combine. x+12=13. Subtract x=1. From there, take that and substitute that into what you solved y. y=4-1=3. :)
ACCESS MORE